2017
DOI: 10.1002/jat.3502
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of non‐alcoholic fatty liver disease in male rat offspring exposed to fluoxetine during fetal and neonatal life involves the NLRP3 inflammasome and augmented de novo hepatic lipogenesis

Abstract: Up to 10% of women take selective serotonin reuptake inhibitors (SSRI) during pregnancy. Children exposed to SSRIs in utero have an increased risk of being overweight suggesting that fetal exposure to SSRIs can cause permanent metabolic changes. We have previously shown in rats that fetal and neonatal exposure to the SSRI antidepressant fluoxetine results in metabolic perturbations including increased hepatic triglyceride content; a hallmark of non‐alcoholic fatty liver disease (NAFLD). Therefore, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
(99 reference statements)
1
2
0
Order By: Relevance
“…In the present study, in vitro and in vivo HAT assays clearly showed the TA inhibits HAT-induced histone acetylation. The acetylation of histone H3K9 is well known as an epigenetic marker for NAFLD [47], [50], and, as previously remarked, acetylation of proteins is associated with dynamic cellular activities in the liver [46]. In addition, we showed that TA attenuated the lipid accumulation-induced increase in acetylation levels of total proteins and histones H3K9 and H3K36 in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, in vitro and in vivo HAT assays clearly showed the TA inhibits HAT-induced histone acetylation. The acetylation of histone H3K9 is well known as an epigenetic marker for NAFLD [47], [50], and, as previously remarked, acetylation of proteins is associated with dynamic cellular activities in the liver [46]. In addition, we showed that TA attenuated the lipid accumulation-induced increase in acetylation levels of total proteins and histones H3K9 and H3K36 in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…FLX and DNP are other two positive control drugs used in this study to observe the behavioral performance of rats. However, lipid metabolism abnormalities have been reported in patients with depression treated with FLX (41) and patients with AD treated with DNP (42), and increased incidence of NAFLD has been found in male rat offspring exposed to FLX during the fetal and neonatal periods (43). In the present study, they showed no effect on the increased plasma glucose and lipid concentrations and the morphological and functional impairments in the liver of NAFLD rats.…”
Section: Discussionmentioning
confidence: 99%
“…( 33 ) In rat models, fetal and neonatal exposure to fluoxetine increased the incidence of NAFLD; changes in the inflammasome and hepatic lipogenesis were observed and were considered possible mechanisms. ( 34 ) Interestingly in our analysis, controlling for serotonergic medications did not cause this metabolite to lose statistical significance, suggesting that exogenous serotonin is not the cause of this observed association between serotonin metabolites and liver‐related events. Given that serotonin modulation is already possible through existing therapies, better understanding of the relationship between serotonin and NAFLD could have direct applications to patient care.…”
Section: Discussionmentioning
confidence: 58%